Study on Load Capacity Limits of Flanged Pressure Vessel Nozzles - Stikvoort, Walther (Novel Perspectives of Engineering Research Vol. 1, 2021)
When designing pressure vessels, it is quite important to know the loads exerted on the nozzle by the connecting pipework. However the piping reactions computed by the piping structural analysis are often not available at the vessel design stage. To overcome this problem, the pressure vessel must be exclusively designed for the internal design pressure, after which the permissible external loads for the nozzle- vessel intersection as well as for the nozzle-piping connection (flange) can be calculated. In this way the load limits and load capacity of the nozzle can be determined and are available at an early stage to the piping designer (pipe stress analyst). Successively it is the responsibility of the piping designer to ensure that the piping reactions are kept within the permissible load limits of the pressure vessel nozzle. The advantage of this approach is that the imposed loads does not necessitate thickening of the pressure retaining shell of the vessel nor require additional reinforcing pads around the nozzle neck. Moreover it should be noted that by increasing the vessel shell thickness or adding a reinforcing pad, the nozzle becomes more rigid and therefore a better approximation to a fixed point or anchor thus effectively eliminating the advantage of any nozzle flexibility. This approach avoids remedial work of pressure vessels and/or pipework at late stages of a project, which for sure has negative impact on project costs and schedule. In summary, the objective of this study is to ensure that the pipe stress analyst has access to individually allowable nozzle loads at an early stage of the project. The developed algorithm described in Table 1 thru 4 can be used for this task. By applying the load interaction rule, the pipe stress analyst can evaluate the piping reactions computed with the aid of formal pipe stress analysis software.